Impact of artificial light on photosynthesis, evapotranspiration, and plant growth in plant factories: Mathematical modeling for balancing energy consumption and crop productivity - Mohammad Hossein Amirshekari; Mohammad Fakhroleslam (Smart Agricultural Technology)
The impact of artificial light conditions on plants is multifaceted and depends on various influencing factors. Toward optimized energy consumption, understanding the specific requirements of the plant species and tailoring artificial lighting to that, may lead to optimized growth, evapotranspiration (ET), and photosynthetic processes in controlled environments such as indoor farming or plant factories. In this study, an integrated mathematical model has been established to describe relationships between lighting conditions and plants’ growth, ET, and photosynthesis. The developed model also includes the calculation of lamps energy loss, which affects the temperature of the plant factory, and an empirical model for leaf area index (LAI). Additionally, an empirical relationship between plant weight and LAI was developed using experimental data for lettuce plants (Lactuca sativa L.). Key parameters related to photosynthesis and ET for lettuce plants were also accurately adjusted, and the validation results were discussed. Based on the developed model, the effects of light intensity and photoperiod on photosynthesis, LAI, plant weight, and ET were analyzed. Results demonstrate that the effect of the photoperiod on photosynthesis and ET is significantly greater than its effect on plant weight and LAI. However, the impact of light intensity on photosynthesis, ET, plant weight, and LAI is approximately the same. The proposed integrated model can be used to simulate microclimate conditions, optimize resource use, and improve the control of plant factories.